Synthesis of Novel 1,2,3-Triazole-Dihydropyrimidinone Hybrids Using Multicomponent 1,3-Dipolar Cycloaddition (Click)–Biginelli Reactions: Anticancer Activity - Carreiro, Elisabete P.; Sena, Ana M.; Puerta, Adrián; Padrón, José M.; Burke, Anthony J. (Synlett, 2020)
In this work, 21 novel (1,4-disubstituted 1,2,3-triazole)-dihydropyrimidinone (1,2,3-trzl-DHPM) type hybrids were synthesized and characterized. These were divided into two types: hybrids A (5 in total) containing the dihydropyrimidinone heterocyclic ring decorated with a 1,4-disubstituted 1,2,3-triazole in the C-5 position [these compounds were accessed by a multicomponent copper(I)-catalyzed azide alkyne cycloaddition (CuAAC) (or click)–Biginelli reactions with satisfactory yields (39–57%)] and hybrids B (16 in total) containing two 1,2,3-triazole units in the C-5 and C-6 methyl position of the DHPM. Hybrids B were synthesized via functionalization of the C-6 methyl group of hybrids A, a multistep sequence of reactions was used that included bromination, azidation, and a CuAAC. Hybrids B were obtained in very good to excellent yields (up to 99%). Some hybrids A and B were evaluated for their antiproliferative activity against different cancer cell lines that included A549 and SW1573 (non-small-cell lung), HBL-100 and T-47D (breast), HeLa (cervix) and WiDr (colon). Three of these hybrids were potent cell proliferation inhibitors of non-small-cell lung cancer, cervix cancer, breast cancer, and colon cancer.
Keywords: hybrids; 1,2,3-triazole; dihydropyrimidinone; click reaction; Biginelli reaction; one-pot; cancer; antiproliferative